China’s Polytechnic Transformation - Hayhoe, Ruth; Qiang, Zha (International Higher Education, 2010)
In China, after the revolution of 1949, the percentage of engineering enrollments rose, and polytechnic universities have also developed. China's top polytechnic universities have unique advantages with governmental support for serving national competitiveness. The greatest disadvantage faced by polytechnic universities is their limited curricular coverage of areas outside the sciences and engineering.